A high-strength and high-conductivity Cu-Ag-Sn alloy and a preparation method thereof

By adding low melting point Sn elements to the Cu-Ag alloy and performing appropriate heat treatment, the precipitation method of Ag nanophase is changed, and the segregation problem caused by the high melting point of the third component in the prior art is solved, and the high strength and high conductivity of the Cu-Ag-Sn alloy are achieved.

CN116162820BActive Publication Date: 2025-04-08NORTHEASTERN UNIV CHINA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310068943.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-06
Publication Date
2025-04-08
Estimated Expiration
2043-02-06

AI Technical Summary

Technical Problem

The third component added to the existing Cu-Ag alloy has a high melting point and is difficult to dissolve evenly in smelting, resulting in segregation problems and limiting the industrial application of the alloy.

Method used

The Sn element with a low melting point is used as the third component, and the appropriate heat treatment process is used to make the Sn and Ag elements first dissolve into the Cu matrix, and then the Ag precipitation is performed by aging heat treatment, changing the precipitation method of the Ag nanophase, and improving the strength and conductivity of the alloy.

Benefits of technology

Through the addition of Sn element, the strength and conductivity of Cu-Ag-Sn alloy are significantly improved, the third component segregation problem is solved, and the overall performance of the alloy is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004063329400000011
    Figure HDA0004063329400000011
  • Figure HDA0004063329400000012
    Figure HDA0004063329400000012
  • Figure HDA0004063329400000021
    Figure HDA0004063329400000021
Patent Text Reader

Abstract

The invention discloses a Cu-Ag-Sn alloy with high strength and high conductivity, wherein the alloy composition is Ag3-9%, Sn0.1-1%, Y0.01-0.02% by mass percentage, and the remainder is Cu. The preparation method comprises: adding trace Sn elements and Y elements in the form of Ag-Sn master alloy and Ag-Y master alloy, and the remaining Cu and Ag are made of pure metal ingredients; preparing alloy ingots by vacuum induction melting and casting; saturating Sn and Ag elements are solid-dissolved in Cu matrix by solution heat treatment, and then precipitating Sn and Ag elements into nanophase by aging heat treatment. The method can prepare a Cu-Ag-Sn alloy with a large proportion of continuous Ag nano-precipitated phase and uniform organization. The alloy has a hardness of 80-130HV, a strength of 180-250MPa, a conductivity of 70-85%IACS, excellent mechanical and electrical properties, a simple preparation process, and good industrialization prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonferrous metal alloys, and in particular relates to a high-strength and high-conductivity Cu-Ag-Sn alloy and a preparation method thereof. Technical Background

[0002] Copper alloy has good electrical conductivity and is a key material used in important industries such as lead frames, electrical contacts, and strong magnetic coils. Cu-Ag alloy can improve the strength of the alloy because Ag precipitates in nanophase during aging treatment, making the alloy have both high strength and high conductivity. However, Ag is expensive, which greatly increases the cost of the alloy. Therefore, an Ag content of less than 6% by mass is generally used.

[0003] With the continuous development of modern industry, the strength of current Cu-Ag alloys has gradually failed to meet the needs of technological development. For Cu-Ag alloys with an Ag weight percentage of 3-9%, the main strengthening method relies on the Ag nano-precipitation phase precipitated in the Cu matrix after aging heat treatment. Ag nano-precipitation phases can be divided into two categories: continuous precipitation phases and discontinuous precipitation phases; discontinuous precipitation phases are coarse flakes or rods, while continuous precipitation phases are fine dispersed particles distributed in a network. And the continuous precipitation phase is small in size and has a large distribution density. Related studies have shown that promoting the continuous precipitation phase in Cu-Ag alloys is beneficial to improving the strength and hardness mechanical properties of the alloy. The continuous precipitation phase can form high-density Ag reinforcing fibers after deformation processing, which is the key to improving the strength of high-strength and high-conductivity Cu-Ag composite materials. Therefore, how to increase the proportion of Ag continuous precipitation phases and refine the size of precipitation phases has become the key to improving the mechanical properties of Cu-Ag alloys with 3-9% Ag content.

[0004] At present, the performance of the alloy can be further improved by adding a third component to optimize the alloy composition and change the morphology of the nano-precipitated phase. Invention patent 201610218372.0 discloses a method for preparing a Cu-Ag-Fe alloy by combining a 0.1-30T magnetic field with the addition of Fe elements, and the resulting Cu-Ag-Fe alloy wire / plate has a conductivity of 55-88% IACS and a tensile strength of 750-1760 MPa. Invention patent 201810259998.5 discloses a method for preparing a Cu-Ag-Fe-C alloy, adding Fe-C pre-alloy during the smelting process of the Cu-Ag alloy to uniformly distribute the Fe-C pre-alloy particles, improve the electrical conductivity and tensile strength of the alloy, and obtain a cast alloy with a tensile strength of 420-500 MPa and a conductivity of 40-55% IACS. Invention patent 201910401815.3 discloses a high-strength and high-conductivity Cu-Ag-Sc alloy and its preparation method. Ag-Sc master alloy is added during the smelting process. The continuous precipitation of Ag is promoted by adding Sc. The alloy hardness is 88-148HV and the conductivity is 83-88% IACS. Invention patent 201610173651.X discloses adding Nb, Cr or Mo as a third component to Cu-Ag alloy (6-30% Ag), strengthening the alloy by dispersion strengthening, controlling the precipitation of Ag by appropriate heat treatment, promoting the continuous precipitation of Ag, improving the strength of the material and increasing the conductivity; Invention patent 200510048639.8 discloses that the Cu-Ag alloy structure is refined by adding RE, and large deformation and reasonable thermomechanical treatment are used to form an in-situ nanofiber reinforced composite material with Ag nanofiber as the reinforcement phase, so that its tensile strength and conductivity performance are optimized. Invention patent 202110851495.9 discloses a high-strength, high-conductivity, high-heat-resistant Cu-Ag-Hf alloy and a preparation method. By adding Hf to the Cu-Ag alloy, a better precipitation strengthening effect is obtained, so that the softening resistance temperature of the alloy is not less than 550°C. In the above patents, the melting points of the added third components are relatively high, and it is difficult to evenly dissolve into the Cu-Ag alloy melt during smelting, which is prone to segregation, which is not conducive to the preparation of industrial large-size cast alloys and limits the application value.

[0005] Some academic literature has also discussed the improvement of performance by adding a third component to Cu-Ag alloys; among them, Raabe D et al. (Acta materialia. 1999, 47 (3): 769) found that the Nb-rich phase has good ductility, which makes the Cu-8.2% Ag-4% Nb ternary alloy have good ductility, and at the same time has high linear strain and ultimate tensile strength. Wu X et al. (Materials & Design. 2019, 168: 107676) reported that adding Zr to Cu-Ag alloys can improve the mechanical properties of the alloy after high temperature annealing. Bittner F et al. (Materials Science and Engineering: A. 2014, 597: 139) found that Zr can form high-hardness Cu4AgZr composite particles in Cu-Ag alloys, which can improve the hardness of Cu-Ag-Zr composite materials. LiR et al. (Journal of Alloys and Compounds. 2019, 773: 121) reported that adding 0.1% Fe to Cu-26% Ag alloy can refine the eutectic structure and Ag precipitation phase, thereby improving the tensile strength and resistivity of the alloy. Chang L et al. (Journal of Rare Earths. 2017, 35 (10): 1029) reported that adding rare earth element Ce to Cu-Ag alloy can promote the transformation of cast Cu-Ag alloy columnar crystals to equiaxed crystals, refine the alloy grains, and harden the precipitation phase, thereby improving the mechanical properties of the alloy. The third elements added in the above literature are also elements with melting points much higher than Cu and Ag. In the preparation of large-size ingots for industrial production, smelting difficulties and macro-segregation problems are prone to occur, limiting the value of application. Summary of the invention

[0006] In view of the prior art, the melting points of the third components added are relatively high, such as the melting points of Sc element is 1541°C, Fe is 1538°C, Cr is 1907°C, Nb is 2468°C, Mo is 2620°C, etc., which makes it difficult for the added elements to be uniformly dissolved into the Cu-Ag alloy melt during smelting, and segregation is easily generated, which is not conducive to the preparation of industrial large-scale cast alloys, limiting the value of its application. The purpose of the present invention is to propose a high-strength and high-conductivity Cu-Ag-Sn alloy and a preparation method thereof. With the Sn element having a melting point of 232°C as the third component, with appropriate heat treatment process, the Sn and Ag elements are first dissolved into the Cu matrix through heat treatment, and then the Ag is precipitated through aging heat treatment. The precipitation mode of the Ag nanophase is changed by the Sn element, and a Cu-Ag-Sn alloy with high strength and high conductivity is obtained.

[0007] A high-strength and high-conductivity Cu-Ag-Sn alloy is composed of the following components by mass percentage: 3-9% Ag, 0.1-1% Sn, 0.01-0.02% Y, and the balance is Cu.

[0008] Furthermore, the alloy has a tensile hardness of 80 to 130 HV, a strength of 180 to 250 MPa, and an electrical conductivity of 70 to 85% IACS.

[0009] Another object of the present invention is to provide a method for preparing a high-strength and high-conductivity Cu-Ag-Sn alloy, comprising the following steps:

[0010] (1) placing solid raw materials of oxygen-free Cu, high-purity Ag, Ag-Sn master alloy and Ag-Y master alloy in a crucible of an induction melting furnace, evacuating the induction melting furnace, introducing an inert gas, heating to 1200-1300° C. under the protection of the inert gas, and keeping the temperature for 10-30 min to obtain an alloy melt, turning off the induction power supply, allowing the melt to stand for 30 seconds, and then casting the alloy liquid into a mold to obtain an alloy ingot.

[0011] (2) Under inert atmosphere conditions, the alloy ingot is heated to 780-800°C, kept at this temperature for 1-4 hours, and then water quenched to room temperature to obtain a heat-treated alloy ingot.

[0012] (3) Under inert atmosphere conditions, the heat-treated alloy ingot is heated to 400-450°C, kept at this temperature for 2-4 hours for aging heat treatment, and then air-cooled to room temperature to produce a high-strength and high-conductivity Cu-Ag-Sn alloy.

[0013] Preferably, the vacuuming condition in step (1) is a vacuum degree ≤ 0.1 MPa.

[0014] Preferably, the inert gas described in step (1) is argon, and the inert gas pressure is ≤0.05 MPa.

[0015] Furthermore, the Ag-Sn master alloy in step (1) is prepared by the following method: the high-purity Ag is heated to 1000° C. in an induction heating furnace, metallic Sn is added, and after the alloy liquid is completely mixed, it is cast into a small ingot to obtain the Ag-Sn master alloy; the mass percentage of Sn in the Ag-Sn master alloy is 5 to 20%.

[0016] Furthermore, the Ag-Y master alloy in step (1) is prepared by the following method: the high-purity Ag and metal Y are placed in an electric arc furnace, heated to above 1600° C., and cooled in the furnace to form a small ingot to obtain the Ag-Y master alloy; the mass percentage of Y in the Ag-Y master alloy is 1 to 5%.

[0017] Furthermore, the alloy melt is stirred by electromagnetic induction while the heat preservation in step (1) is carried out to obtain a uniformly mixed alloy liquid.

[0018] Preferably, the inert atmosphere is an argon atmosphere.

[0019] The present invention unprecedentedly adds Sn and Y into the Cu-Ag alloy to change the nanophase precipitation mode to obtain a high-strength and high-conductivity Cu-Ag-Sn alloy and its related preparation method. Compared with the prior art, it has the following advantages:

[0020] ① The third component Sn has a low melting point and is easy to be evenly dissolved into the Cu-Ag alloy melt during smelting. After solidification, the Sn element is evenly distributed in the Cu-Ag-Sn alloy ingot, solving the segregation problem of the third component in the Cu-Ag alloy.

[0021] ②Sn element has a large solid solubility in Cu, and can be dissolved in the Cu matrix together with Ag, and then precipitated together with Ag by aging, which can effectively change the precipitation mode of Ag and promote the distribution of Ag in the Cu matrix in the form of continuous precipitation phase. This makes the strength and hardness of Cu-Ag-Sn alloy significantly higher than that of Cu-Ag alloy under the same conditions.

[0022] ③ By using Ag-Sn master alloy, the burning and volatilization of low melting point Sn component is avoided.

[0023] ④ Through Ag-Y master alloy, Y is evenly distributed in the melt. During the smelting process, Y element can combine with oxygen element to form oxide slag that floats up and is removed, effectively removing impurity O element (removal of O element in the alloy can improve the conductivity of the alloy). The remaining small amount of Y element in the alloy after solidification is ≤0.02%, with Cu 7 The Y compound is dispersed in the tissue in the form of particles and plays a role in further strengthening the matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope metallographic image of the Cu-6Ag-0.2Sn alloy prepared in Example 4 of the present invention.

[0025] Figure 2 This is a scanning electron microscope metallographic image of the Cu-6Ag-0.1Sn alloy prepared in Example 5 of the present invention.

[0026] Figure 3 This is a scanning electron microscope metallographic image of the Cu-6Ag alloy prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The embodiments of the present invention use a four-point probe method to detect the electrical conductivity of the alloy, use a tensile machine to detect the tensile strength of the alloy, and use a Vickers hardness tester to measure the hardness of the alloy.

[0028] The following non-limiting embodiments can enable ordinary technicians in the field to more fully understand the present invention, but do not limit the present invention in any way. Non-essential improvements and adjustments made by technicians in the field based on the above-mentioned invention content still fall within the scope of protection of the present invention.

[0029] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0030] Example 1

[0031] The preparation method of the high-strength and high-conductivity Cu-Ag-Sn alloy in this embodiment comprises the following steps in sequence:

[0032] (1) Solid raw materials of oxygen-free Cu, high-purity Ag, Ag-Sn master alloy and Ag-Y master alloy are placed in a crucible of an induction melting furnace, wherein the weight percentage of each element is: Ag is 6%, Sn is 0.5%, Y is 0.05%, and the balance is Cu. The induction melting furnace is evacuated to a vacuum degree of ≤0.1MPa. An inert gas is then introduced into the furnace for protection, and the inert gas pressure is ≤0.05MPa. The alloy melt is heated to 1200°C to obtain the alloy melt, and the heat is maintained for 10 minutes. While the heat is maintained, the melt is stirred by electromagnetic induction to obtain a uniformly mixed alloy liquid. The alloy liquid is cast into a mold to obtain a Cu-Ag-Sn alloy ingot.

[0033] (2) In an argon atmosphere heat treatment furnace, the alloy ingot is heated to 780°C, kept at this temperature for 4 hours for heat treatment, and then quenched with water to room temperature to obtain a heat-treated Cu-Ag-Sn alloy ingot having a uniform structure in which all Ag and Sn elements are dissolved in the Cu matrix.

[0034] (3) In an argon atmosphere heat treatment furnace, heat the heat-treated alloy ingot to 400°C, keep it warm for 2 hours for aging heat treatment, so that the Ag element precipitates in the form of nanophase, and then air-cool it to room temperature to produce a high-strength and high-conductivity Cu-Ag-Sn alloy. The final actual composition of the alloy is 5.97% Ag, 0.49% Sn, 0.01% Y, and the balance is Cu. The alloy has a hardness of 128HV, a strength of 245MPa, and a conductivity of 78%IACS.

[0035] Example 2

[0036] The method is the same as in Example 1, except that:

[0037] (1) The content of each element by weight is: Ag is 3%, Sn is 0.1%, Y is 0.05%; the balance is Cu.

[0038] (2) Vacuum induction melting step: heating to 1200°C to obtain alloy melt, and keeping the temperature for 10 minutes.

[0039] (3) In the solution heat treatment step, the alloy ingot is heated to 790°C and kept at this temperature for 1 hour for heat treatment.

[0040] (4) In the aging heat treatment step, the alloy ingot is heated to 420°C and kept at this temperature for 3 hours for aging heat treatment. The final actual composition of the alloy is 2.98% Ag, 0.09% Sn, 0.01% Y, and the balance is Cu. The alloy has a hardness of 82 HV, a strength of 181 MPa, and a conductivity of 86% IACS.

[0041] Example 3

[0042] The method is the same as in Example 1, except that:

[0043] (1) The content of each element by weight is: Ag is 9%, Sn is 1%, Y is 0.1%; the balance is Cu.

[0044] (2) Vacuum induction melting step: heating to 1300°C to obtain alloy melt, and keeping the temperature for 30 minutes.

[0045] (3) In the solution heat treatment step, the alloy ingot is heated to 800°C and kept at this temperature for 2 hours for heat treatment.

[0046] (4) In the aging heat treatment step, the alloy ingot is heated to 430°C and kept at this temperature for 4 hours for aging heat treatment. The final actual composition of the alloy is 8.87% Ag, 0.96% Sn, 0.02% Y, and the balance is Cu. The alloy has a hardness of 115 HV, a strength of 220 MPa, and a conductivity of 74% IACS.

[0047] Example 4

[0048] The method is the same as in Example 1, except that:

[0049] (1) The content of each element by weight is: Ag is 6%, Sn is 0.2%, Y is 0.075%; the balance is Cu.

[0050] (2) Vacuum induction melting step: heating to 1250°C to obtain alloy melt, and keeping the temperature for 20 minutes.

[0051] (3) In the solution heat treatment step, the alloy ingot is heated to 780°C and kept at this temperature for 3 hours for heat treatment.

[0052] (4) In the aging heat treatment step, the alloy ingot is heated to 450°C and kept at this temperature for 2.5 hours for aging heat treatment. The final actual composition of the alloy is 5.93% Ag, 0.19% Sn, 0.02% Y, and the balance is Cu. The alloy has a hardness of 95 HV, a strength of 206 MPa, and a conductivity of 82% IACS.

[0053] Example 5

[0054] The method is the same as in Example 4, except that:

[0055] The content of each element by weight percentage is: Ag is 6%, Sn is 0.1%, Y is 0.075%; the balance is Cu.

[0056] The final actual composition of the alloy is 5.91% Ag, 0.09% Sn, 0.02% Y, and the balance is Cu. The alloy has a hardness of 90 HV, a strength of 193 MPa, and a conductivity of 84% IACS.

[0057] Comparative Example 1

[0058] The method is the same as in Example 4, except that:

[0059] The content of each element is as follows by weight percentage: Ag is 6%, and the balance is Cu.

[0060] The final actual composition of the alloy is 5.89% by weight, and the balance is Cu. The Cu-Ag alloy has a hardness of 76 HV, a strength of 166 MPa, and a conductivity of 85% IACS.

[0061] It can be seen from the test results of the above embodiments and comparative examples that after adding Sn and Y elements, although the conductivity of the alloy is slightly reduced, the hardness and strength of the alloy are greatly improved, so that the alloy has better comprehensive performance.

Claims

1. A high-strength and high-conductivity Cu-Ag-Sn alloy, characterized in that: The alloy consists of the following components by mass percentage: Composition: Ag 3-9%, Sn 0.1-1%, Y 0.01-0.02%, the balance is Cu; The alloy has a tensile hardness of 80 to 130 HV, a strength of 180 to 250 MPa, and a conductivity of 70 to 85% IACS; The preparation method of the alloy comprises the following steps: (1) placing solid raw materials of oxygen-free Cu, high-purity Ag, Ag-Sn master alloy and Ag-Y master alloy in a crucible of an induction melting furnace, evacuating the induction melting furnace, introducing an inert gas, heating to 1200-1300° C. under the protection of the inert gas, and keeping the temperature for 10-30 min to obtain an alloy melt, turning off the induction power supply, allowing the melt to stand for 30 seconds, and then casting the alloy liquid into a mold to obtain an alloy ingot; (2) heating the alloy ingot to 780-800° C. under an inert atmosphere, keeping the temperature for 1-4 hours, and then quenching the alloy ingot to room temperature to obtain a heat-treated alloy ingot; (3) Under inert atmosphere conditions, the heat-treated alloy ingot is heated to 400-450°C, kept at this temperature for 2-4 hours for aging heat treatment, and then air-cooled to room temperature to produce a high-strength and high-conductivity Cu-Ag-Sn alloy.

2. The preparation method according to claim 1, characterized in that: The vacuuming condition described in step (1) is a vacuum degree ≤ 0.1 MPa.

3. The preparation method according to claim 1, characterized in that: The inert gas described in step (1) is argon, and the inert gas pressure is ≤0.05MPa.

4. The preparation method according to claim 1, characterized in that: The alloy melt is stirred by electromagnetic induction while maintaining the temperature in step (1).

5. The preparation method according to claim 1, characterized in that: The inert atmosphere is an argon atmosphere.

6. The preparation method according to claim 1, characterized in that: The Ag-Sn master alloy is prepared by the following method: the high-purity Ag is heated to 1000° C. in an induction heating furnace, metallic Sn is added, and after the alloy liquid is completely mixed, small ingots are cast to obtain the Ag-Sn master alloy; the mass percentage of Sn in the Ag-Sn master alloy is 5-20%.

7. The preparation method according to claim 1, characterized in that: The Ag-Y master alloy is prepared by the following method: the high-purity Ag and metal Y are placed in an electric arc furnace, heated to above 1600°C, and cooled in the furnace to form a small ingot to obtain the Ag-Y master alloy; the mass percentage of Y in the Ag-Y master alloy is 1-5%.

Citation Information

Patent Citations

  • Cu-Ag-RE alloy in-situ nano fiber composite material

    CN100365154C

  • A kind of high-strength and high-conductivity copper-based composite material and preparation method thereof

    CN105803246B

  • Preparation method for high-strength high-conductivity Cu-Ag-Fe alloy

    CN105839038A

  • Cu-Ag-Fe-C series alloy and preparation method thereof

    CN108456797A

  • A high-strength, high-conductivity Cu-Ag-Sc alloy and its preparation method

    CN110004320B